Computational Support in Academic Peer Review: An Artificial Intelligence Perspective (ADI Journal on Recent Innovation (AJRI), 2024)
Academic Peer Review is a critical step in the scientific publication process, ensuring the quality and reliability of research work. In this context, this research explores how Artificial Intelligence (AI) can provide valuable computational support in the academic peer review process. This study outlines a perspective that investigates how AI technology can be leveraged to enhance the efficiency, speed, and accuracy of academic peer review. We investigate various methods and tools that can be utilized to support peer review, including the application of machine learning algorithms to identify weaknesses and strengths in manuscripts, as well as the utilization of big data modeling to identify significant research trends. The findings of this research have the potential to pave the way for significant improvements in the academic peer review process, ultimately enhancing the quality of scientific publications and expediting scientific discoveries.